(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
A new anion-exchange granular sorbent was obtained by cross-copolymerization of 1,3,5-triacrylyltriazine with acrylonitrile and its chemical modification with hydroxylamine. In this reaction, hydroxylamine showed a catalytic effect, bringing the static exchange capacity (SEC) of the anion exchanger to 4.7 mg-eq/g. The influence of the concentration of hydroxylamine, temperature and reaction time on the static exchange capacity (SEC) of the anionite was investigated. Carrying out the amination reaction at 95 ° C for 5 h and increasing the hydroxylamine concentration in the reaction mixture to 10 mass% turned out to be the most optimal conditions for modification. The potentiometric titration curves showed that the resulting anion exchange had low basic groups. The ionization constant of the functional groups of the anionite (pK = 7.1), found in the graphic solutions of the Henderson-Hesselbach equation, confirms the low basicity of the anionite. The sorption capacity of the anion exchanger for metal ions from aqueous solutions containing a mixture of Ag+, Pd2+, Pt2+, Cu2+, Sc2+, Ba2+, Sr2+, Ni2+, Co2+, Cd2+, Cr3+ and etc. ions is 10-8 g/l and pH = 5 - 6. It has been established that the new anion exchanger selectively and quantitatively (100%) absorbs Ag+ and Pd2+ ions, which is promising as a selective sorbent for Ag+ and Pd2+ ions.